Peran Sekolah sebagai Agen Sosialisasi dalam Pembentukan Karakter Peserta Didik - Shinta Alfira Ananta; Nurfatiha Nadira; Gusmaneli Gusmaneli (Jurnal Pendidikan Sosial Dan Konseling, 2025)
Schools play a strategic role as agents of socialization in shaping students' character through a planned and continuous educational process. In addition to serving as centers for imparting knowledge, schools also serve to instill moral, religious, disciplined, responsible, and social values ​​through teacher role models, school culture, and the integration of values ​​into the curriculum. However, the implementation of character education in schools still faces several obstacles, such as a lack of consistent application of values, uneven teacher competency in implementing character education, limited supporting facilities, and the negative influence of digital culture on student behavior. Furthermore, the lack of synergy between schools, families, and the community also hinders the reinforcement of values ​​instilled in schools. Therefore, optimizing the role of schools requires targeted strategies, including improving teacher professionalism, strengthening a positive school culture, integrating character education into all subjects, and measurable and ongoing character evaluation. With these steps, schools can be more effective in shaping the character of students with noble character, integrity, and the ability to adapt to an increasingly complex social life.